2014
DOI: 10.1016/j.imavis.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal social withdrawal in depression: Evidence from manual and automatic analyses

Abstract: The relationship between nonverbal behavior and severity of depression was investigated by following depressed participants over the course of treatment and video recording a series of clinical interviews. Facial expressions and head pose were analyzed from video using manual and automatic systems. Both systems were highly consistent for FACS action units (AUs) and showed similar effects for change over time in depression severity. When symptom severity was high, participants made fewer affiliative facial expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 85 publications
10
141
1
Order By: Relevance
“…Such tools are open to a range of subjective biases including the skill and experience of a clinician and the reliability of a patient's own insights on their current mental state [2]. With the aim of enhancing current diagnostic techniques, investigations into new approaches for objectively detecting and monitoring depression based on measurable biological, physiological or behavioural signals are a highly active and growing area of research [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Such tools are open to a range of subjective biases including the skill and experience of a clinician and the reliability of a patient's own insights on their current mental state [2]. With the aim of enhancing current diagnostic techniques, investigations into new approaches for objectively detecting and monitoring depression based on measurable biological, physiological or behavioural signals are a highly active and growing area of research [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Facial expressions convey information about an individual's experience of depression in straightforward ways. For example, Girard and colleagues found that participants with elevated depressive symptoms expressed fewer smiles and more signifiers of disgust [21]. Capturing these indicators of mood in a person's facial expressions has become much more efficient and affordable in recent years with the advent of automated facial analysis [22].…”
Section: Justificationmentioning
confidence: 99%
“…The implicit cues consists of a set of vocal cues (Murray & Arnott 1993) (Girard and Cohn 2014), latency to speak, pauses. These approaches may also be combined in order to have a more natural and error-prone interaction (Lee & Naranyan 2005, Irastorza 2016).…”
Section: Emotion Recognition From Speech Signalsmentioning
confidence: 99%